A green chemistry approach for oxidation of alcohols using novel bioactive cobalt composite immobilized on polysulfone fibrous network nanoparticles as a catalyst - Ramírez-Coronel, Andrés Alexis; Mezan, Salim Oudah; Patra, Indrajit; Sivaraman, Ramaswamy; Riadi, Yassine; Khakberdiev, Shukhrat; Lafta, Holya A.; Abosaooda, Munther; Turki Jalil, Abduladheem; Fakri Mustafa, Yasser (Frontiers in Chemistry, 2022)
In this study, cobalt composite immobilized on polysulfone fibrous network Nanoparticles (CCPSF NPs) was synthesized in a controllable and one-step way under microwave-assisted. The structure of CCPSF NPs was characterized by SEM images (for morphology and size distribution), TGA (for thermal stability), BET technique (for the specific surface area), FTIR (for relation group characterization), and XRD patterns (for crystal size). The oxidation of the primary and secondary alcohols to aldehyde and ketone was investigated by using synthesized CCPSF NPs under solvent-free, microwave-assisted conditions, and high oxidizing activity was observed. In addition to oxidation properties, anticancer activity of the synthesized CCPSF NPs was evaluated by the MTT method on breast cancer, and significant results were obtained.